Pengaruh Bokashi Limbah Tongkol Jagung dan Pupuk Daun terhadap Pertumbuhan dan Hasil Kacang Edamame di Tanah Pasir Pantai - Khavid Faozi; Etik Wukir Tini; Supartoto Supartoto; Rizqianida Arum Cendani (Universitas Sebelas Maret, 2024)
The aim of the study was to determine the dose of corncob waste bokashi and foliar fertilizers application that increased the growth and yield of edamame beans. The research was conducted at the plastic house of the Faculty of Agriculture, Jenderal Soedirman University, Banyumas Regency, Central Java, Indonesia, from November 2020 to January 2021. The pot experiment was arranged in a Randomized Block Design (RBD) with two factors and three replications. The first factor was the level of bokashi consist of 10 (B1), 30 (B2), and 50 t.ha-1 (B3). The second factor was the frequency of foliar fertilizers, i.e control/without treatment (F0), every 5 days (F1), and once every 10 days (F2). Data were analyzed by F test and if significantly different, continued with duncan multiple range test (DMRT) at an error level of 5%. The results showed that the application of corncob waste bokashi increased leaf area by 21.0%, fresh and dry shoot weights 47.9% and 49.0%, fresh and dry root weights 78.5% and 50.3%, number of pods per plant by 45,0%, and pod weight per plant by 58.3%. The application of foliar fertilizer only increased the fresh root weight by 45.4%. There was no interaction between corncob waste bokashi dose and foliar fertilizer frequency on all growth and yield variables of edamame beans.